Rate of sediment accumulation and historic metal contamination in a tidewater glacier fjord, Svalbard. (June 2018) - Mohan, Mahesh; Sreelakshmi, U.; Vishnu Sagar, M.K.; Gopikrishna, V.G.; Pandit, G.G.; Sahu, S.K.; Tiwari, M.; Ajmal, P.Y.; Kannan, V.M.; Abdul Shukkur, M.; Krishnan, K.P.
Abstract: The sedimentation rates in Arctic fjords are influenced by the changes in the glacial inputs. The recent studies have indicated the retreat of glaciers due to climate change and subsequent increase in melt water outflow with high content of debris. The debris may contain natural and anthropogenically originated contaminants. The present study analysed the sedimentation rate in inner Kongsfjorden, Ny-Ålesund, Svalbard using 210 Pb/ 210 Po dating technique. The sedimentation rate ranged between 0.22 and 0.37 cm/year during the last 112 years. The average sedimentation rate obtained was 0.28 cm/y. The rate has been increased during the last 20 years and it might be due to the increased influx of glacial melt water containing debris. Metals and other elements showed an increasing trend towards the surface and observed high deposition rate since 1970s, indicating influence of industrial emissions and it can be a potential threat to Arctic biota. Graphical abstract: Highlights: Glacier melting influences the rate of sedimentation in Arctic fjords. Average sedimentation rate 0.28 cm/year during the last 112 years in Kogsfjorden. The rate has been increased due to the high influx of glacial melt water containing debris. Melt water with debris contains atmospherically deposited contaminants. Recent sediments are having high content of metals.